A scuola di futuro con il Master in «Leadership e Management in Educazione» - Giovanni Moretti (LED Edizioni Universitarie, 2010)
In the School of the Future with the Master in «Leadership and Management in Education» The second-level master's course in «Leadership and Management in Education. The management and governance of education processes and structures in the school of autonomy» has been active in the Faculty of Education Sciences of «Roma Tre» University since 2003. The course is directed by Gaetano Domenici, full professor of Docimology and Director of the Department of the Studies of Educational, Cultural and Intercultural Processes in Contemporary Society. The master takes up the challenge of training future leaders (and managers) for better school governance and to face the near future with greater confidence. The proposal stems from the need to deal with the ever-present risk of interpreting the governance and management of educational processes and institutions as the mere application of norms or the passive implementation of abstract organisational, relational and management models. In this light, particular attention is paid to developing skills to promote educational contexts that can bring together and rebalance the known drives towards the managerialisation of schools and educational institutions with the further, ever more pressing, need for identity, connection with the local territory, and development of the sense of belonging. Participants say they are very satisfied with the course, which is geared to developing the necessary knowledge and operational skills for the strategic management of educational processes in both formal and non-formal contexts.